Islamic Value-Based MSME Mentoring to Increase Micro-Business Competitiveness - Nur’Ainun Gulo; Nurintan Asyiah Siregar; Hazrulta Aulia (International Journal Of Community Service, 2026)
various obstacles, such as low managerial capacity, limited use of digital technology, poor financial record keeping, and suboptimal application of Islamic values ​​in business management. This Community Service (PKM) activity aims to improve the competitiveness of MSMEs through an Islamic-based mentoring program that integrates aspects of business management, digital marketing, financial record keeping, customer service, and Islamic business ethics. The implementation method uses a Participatory Action approach that includes initial observation, outreach, training, mentoring, monitoring, and evaluation. Evaluation is carried out through pre-tests, post-tests, field observations, and interviews. The results of the activity show that the mentoring program has successfully improved the knowledge and skills of participants, indicated by an increase in the average score from 53.54 in the pre-test to 87.40 in the post-test. Observations showed that participants were able to implement simple financial record keeping, utilize digital media as a marketing tool, improve customer service, improve product packaging, and implement Islamic values ​​such as honesty, trustworthiness, fairness, and responsibility in business activities. Interviews also indicated that participants experienced tangible benefits in the form of improved business management skills, increased confidence in marketing products, and increased awareness of the importance of Islamic business ethics as a basis for sustainable business development. Thus, mentoring MSMEs based on Islamic values ​​has proven effective in improving the competence of business actors and strengthening the competitiveness of micro-enterprises in a sustainable manner.